Modest overall survival improvements from 1998 to 2009 in metastatic gastric cancer patients: a population-based SEER analysis - Ebinger, Sabrina Maria; Warschkow, René; Tarantino, Ignazio; Schmied, Bruno; Güller, Ulrich; Schiesser, Marc (Gastric cancer, 2016)
An increasing fraction of gastric cancer patients present with distant metastases at diagnosis. The objective of the present 11-year population-based trend analysis was to assess the survival rates in patients who underwent and in patients who did not undergo palliative gastrectomy.